Penerapan Geometri dalam Perencanaan Instalasi Pengolahan Air Limbah Domestik : Studi Kasus Perumahan Mutiara Sartika, Kota Kendari - Neles Neles; Aryani Adami; Ilham Ilham; Dwiprayogo Wibowo (Al-Ard: Jurnal Teknik Lingkungan, 2020)
The application of a simple geometric concept to design a domestic wastewater treatment plant (WTP) is important because it refers to a three-dimensional spatial structure to construct a storage tank. Thus in this study, we apply a simple geometric system for the design of the reservoir design which can be applied in several simple housing areas (Perumahan Mutiara Sartika-Kendari City). The results show that with the need for clean water consumption of 150 L/day/person with 68 housing types 36 and 5 people/house, the amount of waste generated is 40.8 m3/day. So that the dimensions of the wastewater reservoir built are rectangular with a total volume of 79.1 m3 with an estimated residence time of 29 hours taking into account several functions of the treatment unit. Based on the results of this study, it is hoped that it can help to apply a simple WTP design for housing development.